Zinc metal self-repairing high-performance fibrous flexible aqueous zinc battery and preparation method thereof

By using zinc metal self -repair technology and adsorption additives in flexible water -based zinc batteries, combined with spiral zinc negative and flexible fiber -like positive poles, the short -circulating life of flexible water -based zinc batteries in the complex variable field has achieved a higher problem of higher circulation. Circulation performance and stability.

CN119381591APending Publication Date: 2025-01-28CHINA ELECTRONIC TECH GRP CORP NO 18 RES INST
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411515090.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing flexible water-based zinc batteries have short cycle life in complex deformation scenarios, and the growth of zinc dendrites is intensified, affecting battery performance.

Method used

The high -performance fiber -shaped flexible water -based zinc battery design of zinc metal self -repair is designed. By adding adsorption additives to hydraulic electrolytes, combined with spiral zinc negative and flexible fiber -shaped positive electrodes, the dynamic repair of zinc negative surfaces and the uniform zinc ion uniformly zinc ion uniformity Deposit.

Benefits of technology

It improves the cycle performance of the battery in the complex change scene, extend the cycle life of the battery, inhibit the formation of the Zhiban, and enhance the flexibility and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381591A_ABST
    Figure CN119381591A_ABST
Patent Text Reader

Abstract

The invention provides a zinc metal self-repairing high-performance fibrous flexible aqueous zinc battery and a preparation method thereof, the battery comprises a positive electrode, a zinc negative electrode and a hydrogel electrolyte, the positive electrode and the zinc negative electrode are in a flexible fibrous shape, and the zinc negative electrode is spirally wound outside the positive electrode; the hydrogel electrolyte contains an adsorption type additive, and at least part of the hydrogel electrolyte is arranged between the positive electrode and the zinc negative electrode. The one-dimensional fibrous battery provided by the invention is suitable for weaving and manufacturing wearable electronic fabrics, the flexible fibrous positive electrode and the flexible fibrous zinc negative electrode have good deformation freedom and bending performance, and the hydrogel electrolyte containing the adsorption type additive can be preferentially adsorbed on the surface of the zinc negative electrode when the zinc negative electrode is bent to generate mechanical cracks, so that the mechanical cracks are prevented from being generated. The molecular concentration field distribution and Helmholtz layer components on the surface are changed, and the surface defects are repaired in real time, so that zinc ions are uniformly deposited on the surface of the zinc negative electrode, the formation of dendritic crystals is inhibited, and the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aqueous zinc batteries, and in particular to a zinc metal self-repairing high-performance fibrous flexible aqueous zinc battery and a preparation method thereof. Background Art

[0002] As flexible electronic devices have shown great application potential in the fields of electronic skin and health monitoring, higher requirements are placed on energy storage devices, which need to have the characteristics of high energy density, long cycle life, high mechanical flexibility and environmental friendliness. Flexible batteries with two-dimensional planar structures have low degrees of freedom and are difficult to adapt to actual complex deformation usage scenarios; at the same time, flexible batteries with two-dimensional planar structures are often integrated with existing wearable electronic fabrics by sewing and gluing, ignoring the comfort and moisture conductivity perceived by the human body. In contrast, one-dimensional fiber-type batteries can be deformed freely in multiple dimensions, can adapt to the deformation of clothing during daily behavior, and are expected to connect and cooperate with the current textile industry.

[0003] Among flexible batteries, flexible aqueous zinc batteries have sufficient reserves, low redox potential (-0.763Vvs.SHE) and high theoretical specific capacity (820mAh / g), which has attracted widespread research interest. However, due to the violent side reactions on the zinc metal negative electrode side in the aqueous electrolyte, such as dendrite growth, corrosion / passivation, hydrogen evolution reaction, etc., the cycle life of existing flexible aqueous zinc batteries is short, and usually the capacity will be greatly attenuated or the battery will short-circuit when it is less than 500 times. In particular, fibrous flexible aqueous zinc batteries face complex deformation scenarios, and the cracks caused by mechanical damage to the zinc metal negative electrode further promote the growth rate of dendrites.

[0004] In response to this, scholars have developed negative electrode surface modification and electrolyte engineering methods. Negative electrode surface modification is to build an artificial alloy coating to block the direct contact between water and metallic zinc and regulate the zinc ion flux; however, most of this strategy requires a complex preparation process and may be accompanied by poor adhesion. More importantly, when applied to the field of wearable devices, complex deformation will cause the negative electrode surface modification material to fall off, affecting the specific capacity and life of the battery. Electrolyte engineering is to improve the chemical composition of the negative electrode / electrolyte interface by introducing additives to regulate the solvation structure. However, the mechanical deformation of flexible batteries will undoubtedly damage the solid electrolyte interface layer (SEI film), causing the SEI film to be in an endless cycle of formation and damage, affecting the cycle life of the battery.

[0005] In summary, the flexible aqueous zinc batteries currently used in flexible electronic devices, wearable fabrics, etc. mainly have the following problems:

[0006] (1) Insufficient flexibility and low degree of deformation freedom make it difficult to meet the requirements of deformation complexity and user comfort;

[0007] (2) Existing methods for inhibiting zinc dendrite growth to improve battery cycle life are not suitable for flexible aqueous zinc batteries that require repeated complex deformations;

[0008] (3) Cracks caused by mechanical deformation will intensify the growth of zinc dendrites and affect the cycle life of the battery. Summary of the invention

[0009] The purpose of the present invention is to provide a zinc metal self-repairing high-performance fibrous flexible aqueous zinc battery and a preparation method thereof to solve the problems in the background technology.

[0010] The technical solution of the present invention includes: a zinc metal self-repairing high-performance fibrous flexible aqueous zinc battery, which includes a positive electrode, a zinc negative electrode and a hydrogel electrolyte, the positive electrode and the zinc negative electrode are both flexible fibrous, and the zinc negative electrode is spirally wound outside the positive electrode; the hydrogel electrolyte contains an adsorption-type additive, and at least a portion of the hydrogel electrolyte is between the positive electrode and the zinc negative electrode.

[0011] Preferably, the adsorption additive includes at least one of dimethyl uracil, β-alanine, sodium gluconate and polyethylene glycol.

[0012] Preferably, in the hydrogel electrolyte, the concentration of the adsorption-type additive is 0-0.5M.

[0013] Preferably, the hydrogel electrolyte contains a soluble zinc salt, and the soluble zinc salt includes one of zinc trifluoromethanesulfonate, zinc sulfate and zinc chloride.

[0014] Preferably, in the hydrogel electrolyte, the concentration of the soluble zinc salt is 1-2M.

[0015] Preferably, the hydrogel electrolyte contains a hydrogel, and the hydrogel is made of deionized water and carboxymethyl cellulose.

[0016] Preferably, the positive electrode comprises a fibrous current collector and an active substance on its surface, the fibrous current collector is stainless steel wire, aluminum wire or titanium wire, and the active substance is nano manganese dioxide, ammonium vanadate or polyaniline.

[0017] Preferably, the diameter of the fibrous current collector is 100 μm to 200 μm; and in the positive electrode, the mass linear density of the active material is 5 to 30 μg / cm.

[0018] Preferably, the diameter of the zinc negative electrode is 100 μm to 500 μm.

[0019] The technical solution of the present invention also includes: a method for preparing the zinc metal self-repairing high-performance fibrous flexible aqueous zinc battery as described above, which comprises the steps of:

[0020] Positive electrode preparation: The active material is attached to the fibrous current collector by a slurry coating method to obtain a positive electrode;

[0021] Zinc negative electrode pretreatment: After removing impurities from the surface of the zinc negative electrode, it is wound into a spiral shape;

[0022] Preparation of hydrogel electrolyte: deionized water and carboxymethyl cellulose are mixed and heated, and soluble zinc salt and adsorption additive are dissolved therein to obtain hydrogel electrolyte;

[0023] Battery assembly: Place the spiral zinc negative electrode into a heat shrink tube, inject the hydrogel electrolyte, insert the positive electrode into the center of the zinc negative electrode, seal the end of the heat shrink tube with glue and freeze it to obtain a high-performance fibrous flexible aqueous zinc battery with self-healing zinc metal.

[0024] The beneficial effects of the present invention are as follows: the high-performance fibrous flexible aqueous zinc battery with self-repairing zinc metal provided by the present invention has a one-dimensional fibrous morphology, making it suitable for weaving and manufacturing wearable electronic fabrics; the flexible fibrous positive electrode and zinc negative electrode have good deformation freedom and bending performance; the hydrogel electrolyte containing an adsorption-type additive can be preferentially adsorbed on the surface of the zinc negative electrode when the zinc negative electrode is repeatedly bent to produce mechanical cracks, thereby changing the molecular concentration field distribution and Helmholtz layer composition on the surface of the zinc negative electrode, and dynamically repairing the surface defects generated when the zinc negative electrode is deformed in real time, so that zinc ions are uniformly deposited on the surface of the zinc negative electrode, inhibiting the formation of dendrites, and improving the cycle performance of the battery after complex deformation. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is an overall structural diagram of an embodiment of the present invention;

[0026] Figure 2 This is a result diagram of a double-layer capacitance test using a differential capacitance method using the adsorption-type additive provided by the present invention to construct a three-electrode system;

[0027] Figure 3 It is a schematic diagram of dendrite growth on the zinc negative electrode after complex deformation in a battery prepared according to an embodiment of the present invention with and without an adsorption-type additive;

[0028] Figure 4 The figure is a graph showing the charge and discharge cycle test results of the high-performance fibrous flexible aqueous zinc battery with self-repairing zinc metal prepared in Example 1 of the present invention and the fibrous flexible aqueous zinc battery prepared in Comparative Example 1 at a current density of 0.5 A / g;

[0029] Figure 5 The high-performance fibrous flexible aqueous zinc battery with self-repairing zinc metal prepared in Example 1 of the present invention is bent 90° continuously for 1000 times, and the voltage curve of the battery is discharged before bending, after bending 500 times, and after bending 1000 times;

[0030] Figure 6 The high-performance fibrous flexible aqueous zinc battery with self-repairing zinc metal prepared in Example 1 of the present invention is bent continuously at 90° for 1000 times, and the battery capacity retention rate is measured when the battery is discharged before bending, after bending 500 times, and after bending 1000 times.

[0031] In the figure:

[0032] 1. External packaging structure; 2. Zinc negative electrode; 3. Positive electrode; 4. Hydrogel electrolyte. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with embodiments and drawings:

[0034] Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and comparative examples, and are not intended to limit the scope of protection of the present invention. It should be particularly noted that there may be multiple names for the same organic structure, as long as the structure is within the scope of this patent, it belongs to the protection object of this patent.

[0035] Unless otherwise defined, the raw materials, reagents, etc. in the following examples can be purchased from the market or prepared according to reported methods.

[0036] The embodiment of the present invention provides a high-performance fibrous flexible aqueous zinc battery with self-repairing zinc metal and a preparation method thereof. The battery comprises an outer packaging structure 1, a zinc negative electrode 2, a positive electrode 3 and a hydrogel electrolyte 4. The positive electrode 3 and the zinc negative electrode 2 are both in the form of flexible fibers, and the zinc negative electrode 2 is spirally wound around the positive electrode 3. The hydrogel electrolyte 4 contains an adsorption-type additive, and at least part of the hydrogel electrolyte 4 is between the positive electrode 3 and the zinc negative electrode 2. The outer packaging structure 1 extends in the same direction as the positive electrode 3 and is in the form of fibers, encapsulating the positive electrode 3, the zinc negative electrode 2 and the hydrogel electrolyte 4, so that the battery can be used for weaving and manufacturing wearable electronic fabrics.

[0037] In the fibrous flexible aqueous zinc battery provided in this embodiment, the outer packaging structure 1, the positive electrode 3 and the zinc negative electrode 2 are all constructed into flexible fibers. By controlling the size of each structure, it is suitable for different weaving requirements. By mixing a one-dimensional fibrous battery with ordinary weaving thread, a wearable electronic fabric with high comfort, air permeability and moisture conductivity can be obtained; the zinc negative electrode 2 is in a spirally wound form. Compared with the straight extension form similar to the positive electrode 3, when the battery is bent and deformed at the same angle, the fiber deformation degree of the zinc negative electrode 2 in the former is low, and the probability of mechanical cracks inducing severe growth of zinc dendrites is lower, which greatly improves the structural stability and cycle performance of the battery. In addition, since the zinc negative electrode 2 may be prone to side reactions and losses, the battery is usually The zinc negative electrode 2 in the battery needs to be over-configured, and increasing the amount of the zinc negative electrode 2 will increase the overall size and flexibility of the battery to a certain extent. In this embodiment, the zinc negative electrode 2 is spirally wound, which can effectively increase the content of the zinc negative electrode 2 in the battery per unit volume, that is, when the zinc negative electrode 2 is equal, the technical solution of this embodiment is adopted, which can effectively reduce the overall size of the battery, improve the space utilization rate and the flexibility of the battery; in this embodiment, the hydrogel electrolyte 4 is used to physically isolate the positive electrode 3 and the zinc negative electrode 2 and to act as a bridge in the electrochemical reaction, thereby avoiding the use of positive and negative electrode separators in conventional batteries, reducing raw material costs and process costs, and at the same time avoiding the risk of leakage of conventional electrolytes during battery deformation, thereby improving the safety performance of the battery.

[0038] The outer packaging structure 1 can be made of insulating, flexible, and sealable materials commonly used in the field of battery preparation. The specific material can be selected according to actual use requirements, and the present invention does not make more specific limitations. For reference, this embodiment uses a heat shrink tube and uses ultraviolet glue to seal the end of the heat shrink tube as the outer packaging structure 1 of the battery.

[0039] The positive electrode 3 includes a fibrous current collector and an active material on its surface. The active material can be attached to the fibrous current collector by a method commonly used in the field of battery preparation, such as a slurry coating method: the active material and a binder, a conductive agent, and a dispersant are mixed to form a positive electrode slurry, which is then coated on the current collector and dried.

[0040] Optionally, the fibrous current collector is a stainless steel wire, an aluminum wire or a titanium wire, and the active material is nano manganese dioxide, ammonium vanadate or polyaniline. More specifically, the diameter of the fibrous current collector should be controlled at 100 μm to 200 μm. The larger the diameter of the fibrous current collector, the larger the diameter after coating the positive electrode slurry, the smaller the deformation freedom, the higher the difficulty of bending, the easier it is to crack when bent, and the positive electrode slurry will fall off at the cracked part. In the positive electrode, the mass linear density of the active material should be controlled at 5 to 30 μg / cm to control the coating thickness of the positive electrode slurry and ensure the adhesion stability of the outermost active material on the fibrous current collector. At the same time, since the conductivity of the positive electrode slurry is weaker than that of the fibrous current collector, if the positive electrode slurry is too thick, it will affect the overall conductivity of the positive electrode, thereby causing the battery polarization to increase.

[0041] The zinc negative electrode 2 can directly use zinc metal fiber (commercial material, directly available), similar to the material selection principle of the fibrous current collector. The diameter of the zinc negative electrode should be controlled at 100μm to 500μm to ensure its deformation freedom, reduce the difficulty of bending, and reduce cracking during bending.

[0042] In the present invention, there is no restriction on the cross-sectional shape of the fiber-shaped current collector and the zinc negative electrode. Due to the limitation of the fiber manufacturing process, the material with a slightly larger target diameter can be directly drawn into a fiber, and its cross section is circular. The material with a slightly smaller target diameter cannot be directly drawn (will be broken), and can be obtained by cutting a metal sheet, and its cross section is square. For example, the zinc metal fiber commonly found on the market has a diameter of 100μm to 200μm and a general cross section of square, and a diameter of 300μm to 500μm and a general cross section of circular.

[0043] The hydrogel electrolyte 4 contains a hydrogel, a soluble zinc salt and an adsorption-type additive. The hydrogel is prepared by mixing and heating deionized water and carboxymethyl cellulose. The soluble zinc salt is pre-dissolved in a small amount of deionized water, added to the hydrogel and mixed, and finally the adsorption-type additive is added to the hydrogel and mixed. Among them, the soluble zinc salt includes one of zinc trifluoromethanesulfonate, zinc sulfate and zinc chloride, and its concentration is 1 to 2M; the adsorption-type additive includes at least one of dimethyl uracil, β-alanine, sodium gluconate and polyethylene glycol. Experiments have found that as the concentration of the adsorption-type additive continues to increase, the improvement of the battery's cycle performance gradually slows down, and no phenomenal performance improvement will occur. When the concentration of the adsorption-type additive is too high, it will even have a negative impact on the discharge performance of the battery. Therefore, the concentration of the adsorption-type additive should be controlled at 0 to 0.5M.

[0044] Among the above-mentioned components, the adsorption-type additive has the physical property of preferentially adsorbing on the surface of zinc metal. During the complex mechanical deformation process of the zinc negative electrode, the adsorption-type additive can dynamically adsorb / desorb, change the molecular concentration field distribution and Helmholtz layer composition on the surface of the zinc negative electrode, and dynamically repair the surface defects generated when the zinc negative electrode is deformed in real time, so that zinc ions are evenly deposited on the surface of the zinc negative electrode, thereby inhibiting the formation of dendrites.

[0045] Reference Figure 2-3 , attached Figure 2 The results of the double-layer capacitance test using the differential capacitance method are shown in the figure below: Figure 3 It is a schematic diagram of dendrite growth on the zinc negative electrode after complex deformation in a battery prepared according to an embodiment of the present invention with / without an adsorption-type additive.

[0046] The differential capacitance method is to test the Mott-Schottky curve of the battery within a certain voltage range, and obtain the capacitance-voltage relationship after fitting and calculation of the data.

[0047] The test steps in this embodiment are: ① construct a three-electrode system, the working electrode is a Zn sheet, the counter electrode is a Pt sheet, and the reference electrode is Ag / AgCl; use sodium sulfate as the solution system, and whether to add an adsorbent additive to the solution system is a variable; ② after the system is stable, test the open circuit voltage; ③ use IMPE-Impedance-Potential technology, with the open circuit voltage as the center, set the starting voltage and the ending voltage in the range of 0.5 to 1V, the amplitude is 10mV, and the step potential is 0.05V; ④ process the data into 1 / C 2 –Potential form.

[0048] In the obtained data point diagram (Attached Figure 2 ), the shape of the data point graph is "peak-shaped", the higher the peak, the higher the 1 / C 2 The larger the value, the smaller the double-layer capacitance C, indicating that the effective electrochemical surface area of ​​the working electrode is reduced, which is the result of the adsorption of functional additives. Figure 3 It can be seen that when the battery is charged and discharged, a large number of zinc dendrites will be produced at the mechanical damage caused by the deformation of the working electrode. The adsorption-type additive has preferential adsorption on the zinc surface, which can passivate the energy field distribution on the working electrode surface and average the current density distribution, so that zinc ions are evenly deposited and the formation of dendrites is inhibited.

[0049] The method for preparing the above-mentioned zinc metal self-repairing high-performance fibrous flexible aqueous zinc battery comprises the following steps:

[0050] (1) Preparation of positive electrode: The active material is attached to the fibrous current collector by a slurry coating method to obtain a positive electrode;

[0051] In this step, a binder, a conductive agent and an active material (which can be purchased or made by yourself) are mixed, a dispersant is added, and the mixture is ground to obtain a positive electrode slurry; the positive electrode slurry is coated on a fibrous current collector and dried to obtain a positive electrode;

[0052] The binder may be PVDF commonly used in the field of battery preparation, and the conductive agent may be conductive carbon black, Super P, carbon nanotubes, etc. commonly used in the field of battery preparation.

[0053] (2) Pretreatment of the zinc negative electrode: After removing impurities from the surface of the zinc negative electrode, it is wound into a spiral shape;

[0054] In this step, when removing impurities from the surface of the zinc negative electrode, use sandpaper with a mesh size of 7000 or above to polish off the oxide layer and oil impurities on the surface of the zinc negative electrode, without leaving obvious scratches that affect the deposition of zinc ions; after polishing, use deionized water and ethanol to ultrasonically clean and then dry;

[0055] When winding, take the embroidery needle as the axis and wind it into a spiral along the longitudinal direction of the embroidery needle.

[0056] (3) Preparation of hydrogel electrolyte: deionized water and carboxymethyl cellulose are mixed, and a soluble zinc salt and an adsorption-type additive are dissolved therein to obtain a hydrogel electrolyte;

[0057] In this step, carboxymethyl cellulose is dissolved in deionized water and vigorously stirred at 60-100° C. for 1 hour or more to obtain a uniform hydrogel;

[0058] Before dissolving the soluble zinc salt in the hydrogel, the soluble zinc salt may be pre-dissolved in a small amount of deionized water and then added to the hydrogel to ensure uniform dispersion of the soluble zinc salt in the hydrogel.

[0059] (4) Battery assembly: The spiral zinc negative electrode is placed in a heat shrink tube, and the hydrogel electrolyte is injected. The positive electrode is inserted into the center of the zinc negative electrode. The end of the heat shrink tube is sealed with glue and then frozen to solidify the hydrogel, thereby obtaining a high-performance fibrous flexible aqueous zinc battery with self-healing zinc metal.

[0060] The diameter of the heat shrink tube is selected according to actual use requirements. The diameter of the heat shrink tube selected in this embodiment is 1 mm to 5 mm.

[0061] The following are some specific embodiments of the present invention.

[0062] Example 1

[0063] Preparation of high-performance fibrous flexible aqueous zinc batteries with self-healing zinc metal

[0064] (1) Synthesis of active material - nano manganese dioxide: 0.755 g of manganese sulfate and 1.35 g of potassium persulfate were dissolved in 100 mL of deionized water; 25 mL of 1.2 M NaOH solution was added and stirred vigorously for 1 hour, and then aged for 1 hour; the supernatant was poured out, and the resulting precipitate was washed with deionized water and ethanol; the precipitate was freeze-dried for 2 days to obtain the final product, nano manganese dioxide.

[0065] (2) Preparation of positive electrode: The prepared nano manganese dioxide, polyvinylidene fluoride, carbon nanotubes and conductive carbon black were uniformly mixed in a mass ratio of 7:1:1:1, and N-methyl-2-pyrrolidone was used as a dispersant. After grinding for 3 hours, a uniform positive electrode slurry was obtained; the prepared positive electrode slurry was coated on the polished fibrous current collector, and vacuum dried at 60°C for 12 hours to obtain a positive electrode; wherein the fibrous current collector was a titanium wire with a diameter of 100 μm, and the mass linear density of the active material was 5 μg / cm.

[0066] (3) Pretreatment of zinc negative electrode: Grind zinc metal fiber with a diameter of 100 μm with 7000-grit sandpaper to remove the oxide layer and oil impurities on its surface, and do not leave obvious scratches that affect the deposition of zinc ions; use deionized water and ethanol ultrasonic cleaning and then dry; use an embroidery needle as the axis, and wind the zinc metal fiber into a spiral along the longitudinal direction of the embroidery needle for later use.

[0067] (4) Preparation of hydrogel electrolyte: 0.8 g of CMC (carboxymethyl cellulose) was dissolved in 20 mL of deionized water, and the mixture was vigorously stirred at 60° C. for 1 hour to obtain a uniform hydrogel; zinc sulfate was taken at a molar concentration of 2 M of the soluble zinc salt in the hydrogel electrolyte, and the zinc sulfate was dissolved in a small amount of deionized water, and then added to the hydrogel and mixed; dimethyl uracil was taken at a molar concentration of 0.2 M of the adsorption-type additive in the hydrogel electrolyte, and dimethyl uracil was added to the hydrogel and mixed to obtain a hydrogel electrolyte.

[0068] (5) Battery assembly: Select a heat shrink tube with a diameter of 2 mm, place the spiral zinc negative electrode into the heat shrink tube, inject the hydrogel electrolyte, install the positive electrode at the axial position of the zinc negative electrode, seal the port with UV glue, and freeze it at -5°C for 12 hours to obtain a high-performance fibrous flexible aqueous zinc battery with self-healing zinc metal.

[0069] Example 2

[0070] Preparation of high-performance fibrous flexible aqueous zinc batteries with self-healing zinc metal

[0071] (1) Synthesis of active material - nano manganese dioxide: 0.755 g of manganese sulfate and 1.35 g of potassium persulfate were dissolved in 100 mL of deionized water; 25 mL of 1.2 M NaOH solution was added and stirred vigorously for 1 hour, and then aged for 1 hour; the supernatant was poured out, and the resulting precipitate was washed with deionized water and ethanol; the precipitate was freeze-dried for 2 days to obtain the final product, nano manganese dioxide.

[0072] (2) Preparation of positive electrode: The prepared nano manganese dioxide, polyvinylidene fluoride, carbon nanotubes and conductive carbon black were uniformly mixed in a mass ratio of 7:1:1:1, and N-methyl-2-pyrrolidone was used as a dispersant. After grinding for 3 hours, a uniform positive electrode slurry was obtained; the prepared positive electrode slurry was coated on the polished fibrous current collector, and vacuum dried at 60°C for 12 hours to obtain a positive electrode; wherein the fibrous current collector was a stainless steel wire with a diameter of 100 μm, and the mass linear density of the active material was 10 μg / cm.

[0073] (3) Pretreatment of zinc negative electrode: Grind zinc metal fiber with a diameter of 100 μm with 7000-grit sandpaper to remove the oxide layer and oil impurities on its surface, and do not leave obvious scratches that affect the deposition of zinc ions; use deionized water and ethanol ultrasonic cleaning and then dry; use an embroidery needle as the axis, and wind the zinc metal fiber into a spiral along the longitudinal direction of the embroidery needle for later use.

[0074] (4) Preparation of hydrogel electrolyte: 0.8 g of CMC (carboxymethyl cellulose) was dissolved in 20 mL of deionized water, and the mixture was vigorously stirred at 60° C. for 1 hour to obtain a uniform hydrogel; zinc trifluoromethanesulfonate was taken at a molar concentration of 2 M of the soluble zinc salt in the hydrogel electrolyte, and the zinc trifluoromethanesulfonate was dissolved in a small amount of deionized water, and then added to the hydrogel and mixed; β-alanine was taken at a molar concentration of 0.1 M of the adsorption-type additive in the hydrogel electrolyte, and β-alanine was added to the hydrogel and mixed to obtain a hydrogel electrolyte.

[0075] (5) Battery assembly: Select a heat shrink tube with a diameter of 2 mm, place the spiral zinc negative electrode into the heat shrink tube, inject the hydrogel electrolyte, install the positive electrode at the axial position of the zinc negative electrode, seal the port with UV glue, and freeze it at -5°C for 12 hours to obtain a high-performance fibrous flexible aqueous zinc battery with self-healing zinc metal.

[0076] Example 3

[0077] Preparation of high-performance fibrous flexible aqueous zinc batteries with self-healing zinc metal

[0078] (1) Synthesis of active material - ammonium vanadate (NH 4 V 4 O 10 ): 2.34 g of NH 4 VO3 Dissolve in 70 mL of deionized water and add 3.782 g of H 2 C 2 O 4 ·2H 2 O and then stirred vigorously; the above solution was transferred to a reactor and heated at 140°C for 48 hours; after cooling to room temperature, the reaction product was washed with deionized water for 3 times and dried at 60°C overnight to obtain ammonium vanadate.

[0079] (2) Preparation of positive electrode: The prepared ammonium vanadate, polyvinylidene fluoride, carbon nanotubes and conductive carbon black were uniformly mixed in a mass ratio of 7:1:1:1, and N-methyl-2-pyrrolidone was used as a dispersant. After grinding for 3 hours, a uniform positive electrode slurry was obtained; the prepared positive electrode slurry was coated on the polished fibrous current collector, and vacuum dried at 60°C for 12 hours to obtain a positive electrode; wherein the fibrous current collector was a titanium wire with a diameter of 200 μm, and the mass linear density of the active material was 20 μg / cm.

[0080] (3) Pretreatment of zinc negative electrode: Grind zinc metal fiber with a diameter of 300 μm with 7000-grit sandpaper to remove the oxide layer and oil impurities on its surface, and do not leave obvious scratches that affect the deposition of zinc ions; use deionized water and ethanol ultrasonic cleaning and then dry; use an embroidery needle as the axis, and wind the zinc metal fiber into a spiral along the longitudinal direction of the embroidery needle for later use.

[0081] (4) Preparation of hydrogel electrolyte: 0.8 g of CMC (carboxymethyl cellulose) was dissolved in 20 mL of deionized water, and the mixture was vigorously stirred at 60° C. for 1 hour to obtain a uniform hydrogel; zinc chloride was taken at a molar concentration of 2 M of soluble zinc salt in the hydrogel electrolyte, and the zinc chloride was dissolved in a small amount of deionized water, and then added to the hydrogel and mixed; sodium gluconate was taken at a molar concentration of 0.3 M of the adsorption-type additive in the hydrogel electrolyte, and sodium gluconate was added to the hydrogel and mixed to obtain a hydrogel electrolyte.

[0082] (5) Battery assembly: Select a heat shrink tube with a diameter of 3 mm, place the spiral zinc negative electrode into the heat shrink tube, inject the hydrogel electrolyte, install the positive electrode at the axial position of the zinc negative electrode, seal the port with UV glue, and freeze it at -5°C for 12 hours to obtain a high-performance fibrous flexible aqueous zinc battery with self-healing zinc metal.

[0083] Example 4

[0084] Preparation of high-performance fibrous flexible aqueous zinc batteries with self-healing zinc metal

[0085] (1) Synthesis of active material - polyaniline: 1.85 mL of aniline was added to 100 mL of hydrochloric acid (concentration: 1 M). After stirring for 1 hour, 1.14 g of ammonium persulfate was added to the above solution under ice bath conditions. The dark green sample was filtered out, washed with deionized water and ethanol, and dried at 60°C for 12 hours to obtain polyaniline.

[0086] (2) Preparation of positive electrode: The prepared polyaniline, polyvinylidene fluoride, carbon nanotubes and conductive carbon black were uniformly mixed in a mass ratio of 7:1:1:1, and N-methyl-2-pyrrolidone was used as a dispersant. After grinding for 3 hours, a uniform positive electrode slurry was obtained; the prepared positive electrode slurry was coated on the polished fibrous current collector, and vacuum dried at 60°C for 12 hours to obtain a positive electrode; wherein the fibrous current collector was an aluminum wire with a diameter of 200 μm, and the mass linear density of the active material was 30 μg / cm.

[0087] (3) Pretreatment of zinc negative electrode: Grind zinc metal fiber with a diameter of 400 μm with 7000-grit sandpaper to remove the oxide layer and oil impurities on its surface, and do not leave obvious scratches that affect the deposition of zinc ions; use deionized water and ethanol ultrasonic cleaning and then dry; use an embroidery needle as the axis, and wind the zinc metal fiber into a spiral along the longitudinal direction of the embroidery needle for later use.

[0088] (4) Preparation of hydrogel electrolyte: 0.8 g of CMC (carboxymethyl cellulose) was dissolved in 20 mL of deionized water, and the mixture was vigorously stirred at 60° C. for 1 hour to obtain a uniform hydrogel; zinc sulfate was taken at a molar concentration of 2 M of soluble zinc salt in the hydrogel electrolyte, and the zinc sulfate was dissolved in a small amount of deionized water, and then added to the hydrogel and mixed; polyethylene glycol was taken at a molar concentration of 0.5 M of the adsorption-type additive in the hydrogel electrolyte, and the polyethylene glycol was added to the hydrogel and mixed to obtain a hydrogel electrolyte.

[0089] (5) Battery assembly: Select a heat shrink tube with a diameter of 5 mm, place the spiral zinc negative electrode into the heat shrink tube, inject the hydrogel electrolyte, install the positive electrode at the axial position of the zinc negative electrode, seal the port with UV glue, and freeze it at -5°C for 12 hours to obtain a high-performance fibrous flexible aqueous zinc battery with self-healing zinc metal.

[0090] Comparative Example 1

[0091] Preparation of fibrous flexible aqueous zinc batteries.

[0092] Compared with Example 1, the only difference is that no adsorption type additive is added to the hydrogel electrolyte of Comparative Example 1.

[0093] Performance Test:

[0094] The high-performance fibrous flexible aqueous zinc battery with self-repairing zinc metal prepared in Example 1 of the present invention and the fibrous flexible aqueous zinc battery prepared in Comparative Example 1 were subjected to charge and discharge cycle tests at a current density of 0.5 A / g. The test results are shown in the attached figure. Figure 4 As shown in the figure, it can be seen that the battery prepared in Example 1 has good cycle life (80% capacity retention rate after 2000 cycles), coulombic efficiency (99.54%) and mass specific capacity. The capacity retention rate of the battery prepared in Comparative Example 1 is reduced to below 80% after 248 cycles, and its coulombic efficiency is also low (96.83%).

[0095] The zinc metal self-repairing high-performance fiber-shaped flexible aqueous zinc battery prepared in Example 1 of the present invention was bent 90° continuously for 1000 times, and the battery was discharged before bending, after bending 500 times, and after bending 1000 times. The test results are shown in the attached figure. Figure 5 and 6 As shown in the figure, it can be seen that after the battery is bent 1000 times, its discharge specific capacity can still be maintained at 91.5% of that before bending, proving that it has excellent flexible electrochemical properties.

[0096] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A high-performance fibrous flexible aqueous zinc battery with self-repairing zinc metal, characterized in that: It comprises a positive electrode, a zinc negative electrode and a hydrogel electrolyte. The positive electrode and the zinc negative electrode are both in the form of flexible fibers. The zinc negative electrode is spirally wound around the positive electrode. The hydrogel electrolyte contains an adsorption-type additive. At least part of the hydrogel electrolyte is between the positive electrode and the zinc negative electrode.

2. The zinc metal self-repairing high-performance fibrous flexible aqueous zinc battery according to claim 1, characterized in that: The adsorption type additive includes at least one of dimethyl uracil, β-alanine, sodium gluconate and polyethylene glycol.

3. The high-performance fibrous flexible aqueous zinc battery with self-repairing zinc metal according to claim 2, characterized in that: In the hydrogel electrolyte, the concentration of the adsorption type additive is 0-0.5M.

4. The high-performance fibrous flexible aqueous zinc battery with self-repairing zinc metal according to any one of claims 1 to 3, characterized in that: The hydrogel electrolyte contains a soluble zinc salt, and the soluble zinc salt includes one of zinc trifluoromethanesulfonate, zinc sulfate and zinc chloride.

5. The zinc metal self-repairing high-performance fibrous flexible aqueous zinc battery according to claim 4, characterized in that: In the hydrogel electrolyte, the concentration of the soluble zinc salt is 1-2M.

6. The high-performance fibrous flexible aqueous zinc battery with self-repairing zinc metal according to any one of claims 1-3 and 5, characterized in that: The hydrogel electrolyte contains hydrogel, and the hydrogel is made of deionized water and carboxymethyl cellulose.

7. The zinc metal self-repairing high-performance fibrous flexible aqueous zinc battery according to claim 6, characterized in that: The positive electrode comprises a fibrous current collector and an active material on its surface. The fibrous current collector is stainless steel wire, aluminum wire or titanium wire, and the active material is nano manganese dioxide, ammonium vanadate or polyaniline.

8. The zinc metal self-repairing high-performance fibrous flexible aqueous zinc battery according to claim 7, characterized in that: The diameter of the fibrous current collector is 100 μm to 200 μm; in the positive electrode, the mass linear density of the active material is 5 to 30 μg / cm.

9. The zinc metal self-repairing high-performance fibrous flexible aqueous zinc battery according to claim 6, characterized in that: The diameter of the zinc negative electrode is 100 μm to 500 μm.

10. A method for preparing a high-performance fibrous flexible aqueous zinc battery with self-repairing zinc metal according to any one of claims 1 to 9, characterized in that: Includes steps: Positive electrode preparation: The active material is attached to the fibrous current collector by a slurry coating method to obtain a positive electrode; Zinc negative electrode pretreatment: After removing impurities from the surface of the zinc negative electrode, it is wound into a spiral shape; Preparation of hydrogel electrolyte: deionized water and carboxymethyl cellulose are mixed and heated, and soluble zinc salt and adsorption additive are dissolved therein to obtain hydrogel electrolyte; Battery assembly: Place the spiral zinc negative electrode into a heat shrink tube, inject the hydrogel electrolyte, insert the positive electrode into the center of the zinc negative electrode, seal the end of the heat shrink tube with glue and freeze it to obtain a high-performance fibrous flexible aqueous zinc battery with self-healing zinc metal.

Citation Information

Cited By

  • Zinc negative electrode modified by telescopic gel interface layer as well as preparation method and application of zinc negative electrode

    CN121709515A